2022
DOI: 10.1155/2022/6141317
|View full text |Cite
|
Sign up to set email alerts
|

An Elevated Neutrophil-to-Lymphocyte Ratio Predicts Poor Prognosis in Patients with Liver Cancer after Interventional Treatments

Abstract: This study is aimed at examining the prognostic value of blood neutrophil-to-lymphocyte ratio (NLR) in patients with hepatocellular carcinoma (HCC). Demographic and clinical data of 543 HCC patients treated with interventional therapies were retrospectively analyzed. Preoperative NLRs were determined and receiver operating characteristic (ROC) curves were plotted for survival time in patients with high (NLR ≥3.8) and low (NLR<3.8) NLR. The median overall survival (OS) was 1241 days after interventional ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…At the same time, platelets play an important role in protecting cancer cells from chemotherapy-induced apoptosis and maintaining the integrity of tumor vasculature (6,22). Lymphocytes include T cells, B cells, and natural killer (NK) cells, which are the main immune cells of the body to kill tumors, and reduction of lymphocytes indicates that patients with PLC have a reduced ability to kill tumor cells (23)(24)(25). Systemic immune inflammation index = (neutrophils * platelets)/ lymphocytes, so when the systemic immune inflammation index is elevated, it indicates an increase in neutrophils and platelets, and a decrease in lymphocyte levels, which indicates that tumor cells are more likely to proliferate and metastasize, resulting in recurrence or metastasis in patients with PLC after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, platelets play an important role in protecting cancer cells from chemotherapy-induced apoptosis and maintaining the integrity of tumor vasculature (6,22). Lymphocytes include T cells, B cells, and natural killer (NK) cells, which are the main immune cells of the body to kill tumors, and reduction of lymphocytes indicates that patients with PLC have a reduced ability to kill tumor cells (23)(24)(25). Systemic immune inflammation index = (neutrophils * platelets)/ lymphocytes, so when the systemic immune inflammation index is elevated, it indicates an increase in neutrophils and platelets, and a decrease in lymphocyte levels, which indicates that tumor cells are more likely to proliferate and metastasize, resulting in recurrence or metastasis in patients with PLC after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Complete blood count-based biomarkers have been shown to correlate well with clinical outcomes in numerous chronic [ 5 , 6 , 7 , 8 , 9 , 10 ], infectious [ 11 , 12 , 13 , 14 , 15 ], and surgical conditions [ 16 , 17 , 18 , 19 , 20 ], as well as in cancer [ 21 , 22 , 23 , 24 , 25 , 26 ]. In particular, the potential role of the red cell distribution width (RDW), a biomarker of the heterogeneity of red blood cells’ size, in predicting adverse events and survival currently represents a topic of intense research in numerous clinical conditions [ 27 , 28 ], including malignancies such as colorectal cancer [ 29 , 30 , 31 ], esophageal cancer [ 32 , 33 ], lung cancer [ 34 , 35 ], breast cancer [ 36 , 37 ], and other malignancies [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“… 14 In 2005, Walsh et al first investigated the predictive value of NLR in colorectal cancer and confirmed NLR as an effective prognostic predictor. 15 In recent years, NLR has also been reported as a powerful prognostic factor in various solid tumours, including non‐small cell lung, 16 breast, 17 liver, 18 and gastric 19 cancers.…”
Section: Introductionmentioning
confidence: 99%